2006
DOI: 10.1016/j.visres.2005.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Stereo and motion information are not independently processed by the visual system

Abstract: Many visual tasks are carried out by using multiple sources of sensory information to estimate environmental properties. In this paper, we present a model for how the visual system combines disparity and velocity information. We propose that, in a first stage of processing, the best possible estimate of the affine structure is obtained by computing a composite score from the disparity and velocity signals. In a second stage, a maximum likelihood Euclidean interpretation is assigned to the recovered affine stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 62 publications
5
72
2
Order By: Relevance
“…In the present investigation, we showed that a disparity-only stimulus elicits the same amount of depth as a velocity-only stimulus when they both provide the same signal-to-noise ratio, regardless of the distal depth magnitudes that have generated the two images. Such empirical results are consistent with the hypothesis that the apparent depth of a stimulus is determined by the magnitude of the retinal signals relative to the uncertainty (i.e., internal noise) arising from the measurement of those signals (Domini & Caudek, 2009;Domini et al, 2006). …”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…In the present investigation, we showed that a disparity-only stimulus elicits the same amount of depth as a velocity-only stimulus when they both provide the same signal-to-noise ratio, regardless of the distal depth magnitudes that have generated the two images. Such empirical results are consistent with the hypothesis that the apparent depth of a stimulus is determined by the magnitude of the retinal signals relative to the uncertainty (i.e., internal noise) arising from the measurement of those signals (Domini & Caudek, 2009;Domini et al, 2006). …”
Section: Resultssupporting
confidence: 86%
“…In the present experiment, in fact, the fixation distance is either 0.5 or 1.0 m, and the visual angle subtended by the stimulus is very small. In these conditions, the horizontal disparities are negligible and, according to our model, they will not affect the perceptual solution recovered from the velocity signals (e.g., Domini et al, 2006). Most importantly, even if binocular vision of the velocity-only stimuli did produce a decrease of the perceived depth extent, such effect could not explain the results obtained in the depth-matching task.…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations